A Systematic Literature Review of Constraint-Based Innovations: State of the Art and Future Perspectives - Agarwal, Nivedita; Grottke, Michael; Mishra, Shefali; Brem, Alexander (IEEE Transactions on Engineering Management, 2017)
The past two decades have seen a tremendous growth in innovation processes conceived under scarcity conditions with special focus on emerging markets and bottom of the pyramid (BOP) customers. However, evolving literature in this field has unfortunately resulted in a multitude of innovation approaches leading to terminology confusion and fragmented literature. Hence, this study is an attempt to systematically organize and synthesize the research on innovation approaches originated in, for or from emerging markets. An extensive systematic review of the existing literature is carried out to investigate the progress of prior research, and to use the insights to define future research pathways. This review is primarily based on the most frequently used innovation approaches, especially frugal innovation, jugaad, disruptive innovation, Gandhian innovation, catalytic innovation, indigenous innovation, bricolage, blowback innovation, trickle-up innovation, resource-constrained innovation, and BOP innovation. Our analysis finds growing standardization in terminology usage and increasing emphasis on “bottom-up” and structured innovation approaches. De-emphasizing the role of technology transfers and spillovers from the West, the findings exhibit increasing applications of these innovations beyond emerging markets to wider markets. Our research results also shed light on the evolution of the topic and instigate further research explorations in the direction of analyzing the user adoption of these constraint-based innovations and understanding the influence of new technological advancements, such as the Internet, mobile telecommunications, and Web 2.0 on the innovation process, with a special focus on the service industr